2012
DOI: 10.1152/ajpcell.00260.2012
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative phosphoproteomics in nuclei of vasopressin-sensitive renal collecting duct cells

Abstract: Vasopressin regulates transport across the collecting duct epithelium in part via effects on gene transcription. Transcriptional regulation occurs partially via changes in phosphorylation of transcription factors, transcriptional coactivators, and protein kinases in the nucleus. To test whether vasopressin alters the nuclear phosphoproteome of vasopressin-sensitive cultured mouse mpkCCD cells, we used stable isotope labeling and mass spectrometry to quantify thousands of phosphorylation sites in nuclear extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 66 publications
2
27
0
Order By: Relevance
“…Previous proteomic studies on vasopressin signaling in kidney collecting duct cells have suggested that the Wnt signaling pathway could also be involved in vasopressin-mediated AQP2 regulation (4,33,34). Recently, Schenk et al (34) demonstrated that vasopressin induced a change in the abundance of the transcriptional regulator ␤-catenin in the nuclear proteome of cortical collecting duct mpkCCD (clone 11) cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous proteomic studies on vasopressin signaling in kidney collecting duct cells have suggested that the Wnt signaling pathway could also be involved in vasopressin-mediated AQP2 regulation (4,33,34). Recently, Schenk et al (34) demonstrated that vasopressin induced a change in the abundance of the transcriptional regulator ␤-catenin in the nuclear proteome of cortical collecting duct mpkCCD (clone 11) cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our laboratory has conducted a series of phosphoproteomic studies to identify proteins whose phosphorylation is regulated by vasopressin in collecting duct cells [22],[55],[18], [19],[56] and in renal thick ascending limbs [57]. An in depth presentation of these results is beyond the scope of the current review.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most consistent phosphoproteomic responses to vasopressin has been a marked increase in β-catenin ( Ctnnb1 ) phosphorylation at Ser552, seen in native IMCD cells [55],[58], in cultured mpkCCD cells [18],[59],[56], and in native thick ascending limb cells [57]. In mpkCCD cells, vasopressin the increase in Ser552 phosphorylation was associated with translocation of β-catenin from the cytoplasm to nucleus, consistent with prior observations in A431 tumor cells [60].…”
Section: Introductionmentioning
confidence: 99%
“…56 Also, phosphorylation of c-Jun in the nucleus is decreased in response to dDAVP. 57 In conclusion, all of these studies suggest an important but ill-defined role for V2R-dependent modulation of MAPK signaling in the renal epithelium.…”
Section: V2r-dependent Mapk Signalingmentioning
confidence: 91%